Intramuscular versus submucosal Dexamethasone injection in surgical extraction of impacted mandibular third molars: Narrative review - SLEIMAN, Mohammad (International Arab Journal of Dentistry (IAJD), 2020)
The aim of this narrative review is to compare the results of different studies concerning the intramuscular route versus the submucosal route for injection of dexamethasone in cases of surgical extraction of mandibular impacted third molars. The advantages and disadvantages of the different techniques will be reported. Studies discussed in this paper revealed that the submucosal route featured so many benefits over the intramuscular one by being simple, comfortable, highly bioavailable, painless, less risky and able to reduce trismus.